(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Kigelia africana or commonly known as the sausage tree is known to be useful in treating stomach problem, pneumonia, toothache, increases production of milk in the lactating woman, treating sores, skin ulcer etc. The aim of this study was to investigate the effect of methanolic stem bark extract of Kigelia africana (SBEka) on liver and kidney function of alloxan-induced diabetic rats. Gas chromatography-mass spectrometry (GC-MS) analysis was carried out on the plant extract which reveals the presence of 52 different chemical constituents that include n-hexadecanoic acid, nonanoic acid, tetradecanoic acid etc. These constituents are believed to various medicinal attributes such as antioxidant, hypocholesterolemic, nematicide, pesticide, antiandrogenic etc. This study shows that alloxan has less effect on the kidney function of albino rats due to the insignificant difference (P<0.05) in urea and creatinine levels between the diabetic control group and the normal control group and the plant extract have less side effect on kidney due to the significant decrease (P<0.05) found in all the kidney parameters except urea. The study also shows that alloxan has toxic effect to the liver function of albino rats due to the significant increase (P<0.05) in AST,ALT and ALP levels, however the plant extract shows hepatoprotective potential due to the significant decrease in those liver parameters. Hence, this study has revealed the effect of alloxan on liver and the plant extract significantly decreases the liver damage